2008
DOI: 10.1038/sj.bjc.6604539
|View full text |Cite
|
Sign up to set email alerts
|

Midkine as a prognostic biomarker in oral squamous cell carcinoma

Abstract: The aim of this study was to evaluate serum midkine (S-MK) concentrations as a prognostic tumour marker in oral squamous cell carcinoma (OSCC). We measured S-MK concentrations in patients with OSCC and healthy volunteers. In addition, we performed real-time quantitative reverse transcription -PCR analysis and immunohistochemistry with fresh tumour samples. To determine whether S-MK concentrations have prognostic value, we performed survival analyses with clinical information by using the log-rank test. Serum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 40 publications
(36 reference statements)
6
45
0
Order By: Relevance
“…In addition, MK expression has been correlated with poor prognosis in patients with neuroblastomas (18), astrocytomas (19), pancreatic cancers (17) and gastrointestinal stromal tumors (20). In a previous study, MK expression was increased in blood samples from OSCC patients and was associated with prognosis (as assessed by 5-year survival) but not with other conventional prognostic factors such as clinical stage, tumor size and cervical lymphnode metastasis (21). That report suggested that the mechanism of the association of MK with prognosis was different from that for tumor proliferation and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MK expression has been correlated with poor prognosis in patients with neuroblastomas (18), astrocytomas (19), pancreatic cancers (17) and gastrointestinal stromal tumors (20). In a previous study, MK expression was increased in blood samples from OSCC patients and was associated with prognosis (as assessed by 5-year survival) but not with other conventional prognostic factors such as clinical stage, tumor size and cervical lymphnode metastasis (21). That report suggested that the mechanism of the association of MK with prognosis was different from that for tumor proliferation and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, we demonstrated downregulation of TESTIN and its association with cancer history and a tendency toward poor survival in head and neck squamous cell carcinoma [96]. The increased serum midkine concentrations were strongly associated with poor survival in early-stage oral squamous cell carcinoma, suggesting it as a useful marker not only for cancer screening but also for predicting prognosis of OSCC patients [97].…”
Section: Genetic and Epigenetic Alterations Of Tsg As Prognostic Biommentioning
confidence: 99%
“…The most intriguing feature of MDK is its massive expression in advanced tumors with high frequency (Qin Li et al, 2011;Kemik et al,2010). Previous reports showed that the blood MDK level is frequently elevated with advance of human carcinomas, decreased after surgical removal of the tumors (Kemik et al,2010;Ota et al, 2008;Lucas et al,2010). Glycosaminoglycan-recognizing activity of human MDK through its C-domain as heparan sulfate trisulfated unit and chondroitin sulfate E unit is important in its mechanism of action.…”
Section: Midkinementioning
confidence: 99%